English as an international language: a review of the literature - García, Raúl Enrique (Colombian Applied Linguistics Journal, 2013)
This article critically reviews and discusses English as an International Language (EIL) as an alternative to the traditional models of English as a Foreign Language (EFL) and English as a Second Language (ESL). The author suggests that the model of EIL is an alternative worthdiscussing in the Colombian context. The article is divided into four different sections: a) EIL, ownership of English and native-speakerism, b) attitudes towards EIL, c) EIL described: What does it look like? and d) EIL and English teaching. The review of the literature evidences that there are still many heated debates on the sociocultural aspect of EIL, that one of the greatest challenges of EIL is the attitudes of English teachers and speakers towards the use and legitimization of non-standard varieties, that there is still much to be done in terms of the description of EIL and that adopting an EIL perspective would imply transforming the ways English is taught. The article concludes with an invitation to the ELT community to initiate the discussion of the potential application of EIL in the Colombian context.